Mendoan as a culinary feature of Banyumasan culture and its relevance as local content material for elementary schools - Rahadini, Astiana Ajeng; Mabruri, Zuniar Kamaluddin; Sotlikova, Rimajon; Choudhury, Anindya Syam (Jurnal Prima Edukasia, 2026)
Mendoan is a traditional Banyumas food that is still preserved to this day. Besides being an icon of Banyumas, mendoan also has a history and symbolic meaning that needs to be understood by the younger generation of Banyumas as a characteristic and identity. The purpose of this study is to identify the history, manufacturing process, and symbolic meaning of Mendoan and its relevance in local content subjects at the elementary school level. This research is a descriptive qualitative research. The data in this study are information from various sources about the history, manufacturing process, and symbolic meaning of mendoan and its relevance in learning. Data sources are informants, events, and documents. Data collection methods are interviews, observation, and document analysis. Data analysis techniques use the Miles and Huberman analysis technique with symbolic meaning using Roland Barthes' theory. The results of the study show that the history of mendoan is related to the accidental origins of making mendoan, the process of making mendoan goes through several stages, and the symbolic meaning of mendoan is related to the meaning of the word mendo in the Banyumasan language which means middle which shows the characteristic of Banyumas society. All of these materials are relevant to be used as local content learning materials for elementary school level. From the research results, it can be concluded that mendoan is a cultural icon of Banyumas. At the same time, preserving and promoting local culture as part of local wisdom learning for elementary school students.